2002
DOI: 10.1097/00003246-200203000-00007
|View full text |Cite
|
Sign up to set email alerts
|

Impaired circadian rhythm of melatonin secretion in sedated critically ill patients with severe sepsis*

Abstract: The present study revealed striking abnormalities in urinary aMT6s excretion in septic ICU patients. In contrast, circadian rhythm was preserved in nonseptic ICU patients, indicating that impaired circadian melatonin secretion in septic patients is mainly related to the presence of severe sepsis and/or concomitant medication. Further investigations are required to examine the underlying pathophysiologic mechanism and the clinical implications of this finding.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
196
5
23

Year Published

2006
2006
2017
2017

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 283 publications
(231 citation statements)
references
References 37 publications
7
196
5
23
Order By: Relevance
“…The central modulation of the immune system and of metabolism is likely to affect the clinical course of sepsis significantly. The septic state includes altered regulation of body temperature, impaired host-defense , abnormal sleep patterns (Mundigler et al, 2002), suppression of appetite (Campbell, 1999), and blunted daily rhythms in behavior and hormonal secretion (Bornstein et al, 1998;Carlson et al, 2006) that are all influenced by the central nervous system.…”
Section: Introductionmentioning
confidence: 99%
“…The central modulation of the immune system and of metabolism is likely to affect the clinical course of sepsis significantly. The septic state includes altered regulation of body temperature, impaired host-defense , abnormal sleep patterns (Mundigler et al, 2002), suppression of appetite (Campbell, 1999), and blunted daily rhythms in behavior and hormonal secretion (Bornstein et al, 1998;Carlson et al, 2006) that are all influenced by the central nervous system.…”
Section: Introductionmentioning
confidence: 99%
“…According to the association between delirium and irregular patterns of melatonin secretion, which has been described by several studies, irregular melatonin secretion could be one of the mechanisms of delirium (10,23,30,31,(50)(51)(52) as well as the presence of sleep deprivation in hospitalized delirious patients at the ICU, as it has been indicated that melatonin and its agonists could be an effective supplement for prevention and management of delirium (38,53,54). Furthermore, several studies have reported the marked improvement of delirium in delirious patients without side effects due to the use of melatonin and ramelteon (6,45,46).…”
Section: Discussionmentioning
confidence: 98%
“…Circadian rhythm may be suppressed during acute inflammatory illness, as evidenced by suppression of circadian clock genes in peripheral leukocytes for at least 17 hours after inoculation of endotoxin in mice (34). This finding may explain why diurnal variation of melatonin was blunted in ICU patients with sepsis compared with ICU patients without sepsis (35). Furthermore, injection of endotoxin disrupted sleep by decreasing non-REM sleep and doubling the amount of wakefulness during the night (36).…”
Section: Circadian Rhythm and Sepsismentioning
confidence: 99%